Laminin Peptide-Immobilized Hydrogels Modulate Valve Endothelial Cell Hemostatic Regulation. - Liezl Rae Balaoing; Allison Davis Post; Adam Yuh Lin; Hubert Tseng; Joel L Moake; K Jane Grande-Allen (PLoS ONE)
Valve endothelial cells (VEC) have unique phenotypic responses relative to other types of vascular endothelial cells and have highly sensitive hemostatic functions affected by changes in valve tissues. Furthermore, effects of environmental factors on VEC hemostatic function has not been characterized. This work used a poly(ethylene glycol) diacrylate (PEGDA) hydrogel platform to evaluate the effects of substrate stiffness and cell adhesive ligands on VEC phenotype and expression of hemostatic genes. Hydrogels of molecular weights (MWs) 3.4, 8, and 20 kDa were polymerized into platforms of different rigidities and thiol-modified cell adhesive peptides were covalently bound to acrylate groups on the hydrogel surfaces. The peptide RKRLQVQLSIRT (RKR) is a syndecan-1 binding ligand derived from laminin, a trimeric protein and a basement membrane matrix component. Conversely, RGDS is an integrin binding peptide found in many extracellular matrix (ECM) proteins including fibronectin, fibrinogen, and von Willebrand factor (VWF). VECs adhered to and formed a stable monolayer on all RKR-coated hydrogel-MW combinations. RGDS-coated platforms supported VEC adhesion and growth on RGDS-3.4 kDa and RGDS-8 kDa hydrogels. VECs cultured on the softer RKR-8 kDa and RKR-20 kDa hydrogel platforms had significantly higher gene expression for all anti-thrombotic (ADAMTS-13, tissue factor pathway inhibitor, and tissue plasminogen activator) and thrombotic (VWF, tissue factor, and P-selectin) proteins than VECs cultured on RGDS-coated hydrogels and tissue culture polystyrene controls. Stimulated VECs promoted greater platelet adhesion than non-stimulated VECs on their respective culture condition; yet stimulated VECs on RGDS-3.4 kDa gels were not as responsive to stimulation relative to the RKR-gel groups. Thus, the syndecan binding, laminin-derived peptide promoted stable VEC adhesion on the softer hydrogels and maintained VEC phenotype and natural hemostatic function. In conclusion, utilization of non-integrin adhesive peptide sequences derived from basement membrane ECM may recapitulate balanced VEC function and may benefit endothelialization of valve implants.